2020
DOI: 10.1016/j.cma.2019.112722
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of an adaptive finite element DtN method for the elastic wave scattering by periodic structures

Abstract: Consider the scattering of a time-harmonic elastic plane wave by a periodic rigid surface. The elastic wave propagation is governed by the two-dimensional Navier equation. Based on a Dirichlet-to-Neumann (DtN) map, a transparent boundary condition (TBC) is introduced to reduce the scattering problem into a boundary value problem in a bounded domain. By using the finite element method, the discrete problem is considered, where the TBC is replaced by the truncated DtN map. A new duality argument is developed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Remark 3.1. We notice that the result and proof of Lemma 3.4 is different from those for the scattering problems in periodic structures [19,27,32]. For the latter problems, the DtN operators are defined on a straight line or plane surface and have only finitely many terms when acting on the incident fields.…”
Section: A Posteriori Error Analysismentioning
confidence: 99%
“…Remark 3.1. We notice that the result and proof of Lemma 3.4 is different from those for the scattering problems in periodic structures [19,27,32]. For the latter problems, the DtN operators are defined on a straight line or plane surface and have only finitely many terms when acting on the incident fields.…”
Section: A Posteriori Error Analysismentioning
confidence: 99%
“…Compared to the PML method, the DtN method can reduce the size of the computational domain. As a viable alternative to the PML method, the adaptive finite element DtN methods have also been developed recently to solve many two-and three-dimensional scattering problems, such as the acoustic scattering problems [26,28,39], the three-dimensional electromagnetic scattering problem [29], and the two-dimensional elastic wave scattering problems [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…This paper concerns the numerical solution of the elastic wave scattering by biperiodic structures in three dimensions. It is a non-trivial extension of the elastic wave scattering by periodic structures in two dimensions [32]. There are two challenges for the three-dimensional problem.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the truncation error decays exponentially with respect to the truncation parameter N . The adaptive finite element DtN method has also been applied to solve the diffraction grating problems [32] as well as the elastic wave equation in periodic structures [26]. The numerical results show that the adaptive finite element DtN method is competitive with the adaptive finite element PML method.…”
mentioning
confidence: 99%